2008
DOI: 10.1002/cjce.20103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shaft eccentricity on the laminar mixing performance of a radial impeller

Abstract: The effects of impeller eccentricity and Reynolds number on the mixing performance were studied for Rushton turbine stirred tank systems operated in the laminar regime (Re < 10). A digital image analysis of an acid-base decolourization reaction was used to characterize the mixing efficiency. Results show that both parameters have remarkable effects on the destruction of the toroidal segregated regions surrounding the Rushton turbine in laminar flow. Criteria are given to prevent the formation of these segregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Forward-reverse agitation could be performed in laminar flow [3,8,9] to minimize the effect of isolated mixing regions or other mixing pathologies. In the turbulent flow regime forward-reverse mixing proceeds more uniformly in the vessel [1,[10][11][12][13][14] but the high shear level of the forward-reverse agitation mode could increase mixing time and mixing power.…”
Section: Introductionmentioning
confidence: 99%
“…Forward-reverse agitation could be performed in laminar flow [3,8,9] to minimize the effect of isolated mixing regions or other mixing pathologies. In the turbulent flow regime forward-reverse mixing proceeds more uniformly in the vessel [1,[10][11][12][13][14] but the high shear level of the forward-reverse agitation mode could increase mixing time and mixing power.…”
Section: Introductionmentioning
confidence: 99%
“…In general, we observed that eccentricity values in the range of E = 0.40–0.47 render flows with practically no segregated areas (globally chaotic flows) with mixing times 95% in the order of 6–8 min at Re < 1. Similarly, in experiments performed in the laminar regime ( Re = 1.5–13.0; using a radial impeller), Cabaret et al (2008) reported the occurrence of practically complete mixing (as evaluated by a similar technique) only in the narrow window of eccentricity values from E > 0.257 to E > 0.56 and 7.5 < Re < 13.0. Indeed, for the lowest Re value where complete mixing was observed ( Re = 7.5), E values in the range of E = 0.39–0.56 were required.…”
Section: Resultsmentioning
confidence: 83%
“…In the laminar regime, concentric tanks agitated with typical axial (Alvarez et al, 2002a), or radial impellers (Alvarez et al, 2005; Cabaret et al, 2008) exhibit extremely impermeable flow separation planes at the impeller height that practically convert the top and bottom sections in independent reactors from the convective point of view (Alvarez et al, 2005; Sánchez‐Cervantes et al, 2006; Zalc et al, 2002). At eccentricity values higher than 0.30, the top–bottom separation is destroyed and therefore, top–bottom circulation is greatly facilitated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to the flow around a rotating disk in a cylindrical casing and the flow around the impeller in a tank, the state of the inner airflow motion around the GyroWheel rotor can be described by the Reynolds number, which is a dimensionless number as shown in (9), where, in fact, the Reynolds number is represented by the ratio of the non-viscous force to the viscous force [29,30]. Meanwhile, the change rate of the air density can be represented by (10), where the spinning angular velocity of the GyroWheel rotor varies under isothermal condition.…”
Section: Numerical Simulationsmentioning
confidence: 99%